The Influence of Intelligence Quotient (IQ), Self-Efficacy and Self-Regulated Learning on the Ability to Memorize Al-Quran - Mustaqimah, Roisatul (Didaktika Religia, 2019)
This article aims to investigate the effect of intellectual intelligence, self-efficacy and self-regulated learning on the ability to memorize the Qur’an. Lately, the Qur’an recitation program has been held in many schools and madrassas. It is hoped that through the process of memorizing the Qur’an, it will be able to shape the personality of the Qur’an on students, which is reflected in their behaviour and mindset so that they are able to strengthen their creeds and strengthen their faith. One of the institutions/madrasa that organizes the Tahfidz al-Qur’an class program as the flagship program is MTs Sunan Ampel Semanding, Tertek Pare. The minimum target for memorization that must be achieved by students is six juz, but in practice, 65% of students can exceed the standard six juz at the end of grade 9. The achievement of memorization that is able to exceed the madrasah target then encourages the writer to conduct research in this place. This research uses a quantitative approach with a path analysis research design. The research sample was all students of grade 8B and 9B, total of 58 students. The instruments used were questionnaire, written test, oral test and documentation. All analyzes were conducted utilizing SPSS (Statistical Product and Service Solution) application Version 21.0. The results showed that of the eight hypotheses that researchers proposed, only two hypotheses showed a significant influence. The remaining six hypotheses show insignificant influence. Two hypotheses that show a significant influence are Self-efficacy on Self-Regulated Learning at 55.7% and Self Efficacy on the ability to memorize the Qur’an by 29.6%.